Envelope for a letter sent by Herman Grimm to A. W. Thayer in Berlin (September 9, 1856?) - Thayer, Alexander Wheelock, 1817-1897:::::::::::::::; Grimm, Herman, 1828-1901::::::::::::::: (2022)
Envelope for a letter sent by Herman Grimm to A. W. Thayer at the Philippstrasse in Berlin (September 9, 1856?)